Sustainability Assessment for Dry, Conventional and Cryogenic Machining in Face Milling of Ti-6Al-4V - IMRAN MASOOD; MIRZA JAHANZAIB; AHMAD WASIM (Mehran University Research Journal of Engineering and Technology, 2017)
Sustainability achievement in difficult-to-machine materials is major concern now-a-days. This paper presents sustainability assessment of machining titanium alloy Ti-6Al-4V. Face milling of Ti-6Al-4V hardened to 55 HRC with PVD (Physical Vapour Deposition) coated inserts was analyzed for dry, conventional and cryogenic cooling modes. Experiments were designed using CCD (Central Composite Design) for modeling and analysis of surface roughness. Feed, speed and depth of cut were used as input parameters. For a specific surface finish, the three cooling modes were compared for cutting power, machining time and material removal rate. The results indicate that cryogenic cooling was more sustainable as compared to dry and conventional cooling process. This sustainable model will help to select sustainable input parameters.